Embodied Routines and Ethnotheories of Morning Drop‐Offs at US and Chinese Preschools. (1st July 2021) - Liu, Chang; Tobin, Joseph
Abstract: This article analyzes scenes from videos of young children being dropped off by their parents or grandparents in Chinese and US preschools. This is an emotionally and cognitively complex event; it asks the child to cross a threshold between the worlds of home and school and the parent or grandparent to turn the care of their child over to teachers. Our analysis suggests that these drop‐off routines reflect complicated interactions of ethnotheories of parenting and child development, implicit cultural pedagogies, changing social pressures and concerns, and affordances and constraints of space and time.